Green Synthesis of Silver Nanoparticles from Psidium Guajava Leaves - Characterization and Evaluation of Synergistic Antibacterial Activity - S.Kiruthika; Lali Growther (International Journal of Pharma and Bio Sciences, 2020)
The applications of nanotechnology are varied. Nanoparticles are used widely because of their tremendous potential. Among the nanoparticles, silver nanoparticles have their own applications. Use of silver has been known since ancient times in literature. They are used in medicine for drug delivery systems, as biosensors and as therapeutic agents. Silver nanoparticles are found to possess antibacterial, antifungal and antiparasitic effects without toxicity. In this study, we describe a simple, low cost effective approach for synthesis of silver nanoparticles using the Psidium guajava leaves extract. Psidium guajava is a medicinal plant used in various ailments. Different parts of the plants are used in traditional medicine. Silver nanoparticles were synthesized and characterized using UV-Vis spectrophotometry, FTIR, SEM, EDX and XRD. The results revealed that the size of the silver nanoparticles were ranged from 20–50 nm. FTIR studies showed the presence of different type of functional groups in silver nanoparticles after reduction. EDX analyses showed the reduction of silver ions and presence of elemental silver. XRD analysis revealed that the synthesized nanoparticles have crystalline form and cubic shape. Antibacterial activity of the synthesized nanoparticles was studied. Synergistic activities of these nanoparticles with antibiotics were also studied and found its enhanced antibacterial activity with coated nanoparticles. Thus, this study showed that these nanoparticles has a wide application in field of medical science to combat antibiotic resistant organisms.